PENGARUH GAME EDUKASI MARKISAH (MARI KITA PILAH SAMPAH) DALAM MENINGKATKAN KEMAMPUAN WASTE MANAGEMENT ANAK USIA 5–6 TAHUN - Zahra Mahbubah; Melia Dwi Widayanti; Fatiha Khoirotunnisa Elfahmi; Sri Widayati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The waste problem remains a serious issue, necessitating the instilling of environmental awareness from an early age. Observations at Puri Cendekia IES Kindergarten indicate that children aged 5–6 years are unable to properly separate organic and inorganic waste, as their practice is limited to disposing of waste appropriately. This study aims to see the efect of the MARKISAH (Let's Sort Waste) educational game to improve children's waste management skills. The pre-experimentmethod used the ADDIE model, involving 14 children in Group B. Data were collected through expert validation, teacher response questionnaires, pretests and posttests. Data were then analyzed descriptively and quantitatively using N-Gain. The results showed that the MARKISAH game was effective, with an N-Gain value of 0.7390 (73.90%), in the high category. Thus, this game is proven to be feasible and effective in helping children understand and correctly separate organic and inorganic waste.